Zinc Contents of Soils and Plants in the Çukurova Region of Turkey - IRMAK, S.; SURUCU, A.K.; AYDIN, S. (Asian Journal of Chemistry, 2010)
Soil, leaf and grain samples were collected from wheat (Triticum spp) fields in Cukurova region of Turkey and the soil samples taken from the root area of plants where the leaf and grain samples were obtained was analyzed for zinc content. The leaf samples taken during the stem elongation and the grain samples taken at the time of maturation were also analyzed for zinc content. The correlation analysis between soil-zinc contents and leaf and grain-zinc contents was performed to determine the relationship among the variables. The analysis findings revealed that the zinc content of soil of Cukurova region was quite low. The zinc content of the soil samples collected in 2005 and 2006 was between 0.16 and 1.10 ppm; 0.16 and 0.88 ppm, respectively. The zinc content of the majority of soil samples was observed below the critical level which is 0.5 ppm. The zinc content of the leaf samples was ranged from 6.10 to 46.10 ppm in 2005 and 15.25 to 25.42 ppm in 2006, whereas the zinc content of the grain samples was ranged from 38.47 to 80.02 ppm in 2005 and 9.24 to 100.31 ppm in 2006. The zinc content of the leaf samples was observed lower than normal, but for grain samples, the findings were relatively better comparing to leaf samples. The zinc content of the leaf and grain samples was directly correlated with the zinc content of the soil. Correlation between zinc content of soil and zinc content of leaf in 2005 is significant at the 0.01 level according to statistical analysis. The extractable P2O5 content of the soil and P content of the grain was, however, inversely correlated with the zinc content of the grain in this study. Correlation between zinc content of grain and P content of grain is significant at the 0.05 level according to statistical analysis.